Implementasi Media Pembelajaran Komik Islam Untuk Meningkatkan Prestasi belajar dalam berpikir Kritis Siswa di Sekolah - Saputro, Anip Dwi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
The goals of this research are : determine learning achievement in students' critical thinking during the learning using the medium of comics Islam. This research is a research experiment using two classes; kontrol one class and one class treatment. In this study using respondents 72 students to test experimental comic learning media Islam. This research aims to improve student achievement in students' critical thinking about the use of pre test, post test and student questionnaire responses. Data from these assessments were analyzed using SPSS. 18.0 with Anacova test. The results showed that: (1) there is a relationship between learning achievement with the critical thinking skills of students because the p value (Sig.) Of